2014
DOI: 10.1364/ol.39.004679
|View full text |Cite
|
Sign up to set email alerts
|

Photo-aligned ferroelectric liquid crystals in microchannels

Abstract: In this Letter we disclose a method to realize a good alignment of ferroelectric liquid crystals (FLCs) in microchannels, based on photo-alignment. The sulfonic azo dye used in our research offers variable anchoring energy depending on the irradiation energy and thus provides good control on the FLC alignment in microchannels. The good FLC alignment has been observed only when anchoring energy normalized to the capillary diameter is less than the elastic energy of the FLC helix. The same approach can also be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…However, the variety of LCs is large. Ferroelectric LCs [24] or lyotropic chromonic LCs for biological sensing application [25,26], are only a few examples of LC materials that might be used in combination with LPFGs to enhance their tuning properties. It could be also interesting to fabricate a LPFG based on the fiber made of high-index glass.…”
Section: Resultsmentioning
confidence: 99%
“…However, the variety of LCs is large. Ferroelectric LCs [24] or lyotropic chromonic LCs for biological sensing application [25,26], are only a few examples of LC materials that might be used in combination with LPFGs to enhance their tuning properties. It could be also interesting to fabricate a LPFG based on the fiber made of high-index glass.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed description of preparation of the photo-aligned MCs infiltrated with FLC material FD4004N has been reported previously. 29 It was demonstrated that the SD1 material gives excellent and stable alignment for FLCs. Based on the results described in the work of Budaszewski et al (2014), 29 we have repeated the procedure of making photo-aligned layer in the PM-1550-01 PCF.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous investigations proved that the exposure energy of ~3 J/cm 2 at wavelength λ = 450 nm would be sufficient to provide the required anchoring energy for FD4004N FLC inside investigated MC. The detailed description of preparation of the photo‐aligned MCs infiltrated with FLC material FD4004N has been reported previously . It was demonstrated that the SD1 material gives excellent and stable alignment for FLCs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high attenuation and sensitivity for damage can be considered as a disadvantage of mPOFs. The vast majority of research studies have been devoted to the infiltration of a PLCF microstructure with nematic LCs, but recently also PLCFs infiltrated with smectic C* LCs have been reported [11].…”
mentioning
confidence: 99%